Importance of SERCA2a on early isolated diastolic dysfunction induced by supravalvular aortic stenosis in rats - Silveira, C.f.s.m.p. (2017)
Cardiac remodeling is defined as changes in shape and function of the heart in response to aggression (pressure overload). The sarcoplasmic reticulum calcium ATPase cardiac isoform 2a (SERCA2a) is a known factor that influences function. A wide spectrum of studies report a decrease in SERCA2a in heart failure, but none evaluate it's the role in early isolated diastolic dysfunction in supravalvular aortic stenosis (AoS). Our hypothesis was that SERCA2a participates in such dysfunction. Thirty-day-old male Wistar rats (60-80 g) were divided into AoS and Sham groups, which were submitted to surgery with or without aorta clipping, respectively. After 6 weeks, the animals were submitted to echocardiogram and functional analysis by isolated papillary muscle (IPM) in basal condition, hypoxia, and SERCA2a blockage with cyclopiazonic acid at calcium concentrations of 0.5, 1.5, and 2.5 mM. Western-blot analyses were used for SERCA2a and phospholamban detection. Data analysis was carried out with Student's t-test and ANOVA. AoS enhanced left atrium and E and A wave ratio, with preserved ejection fraction. Basal condition in IPM showed similar increases in developed tension (DT) and resting tension (RT) in AoS, and hypoxia was similar between groups. After cyclopiazonic acid blockage, final DT was equally decreased and RT was similar between groups, but the speed of relaxation was decreased in the AoS group. Western-blot was uniform in all evaluations. The hypothesis was confirmed, since functional parameters regarding SERCA2a were changed in the AoS group.